ICT in higher education: students perceive increased engagement. (13th April 2015) - Zweekhorst, Marjolein B.M.; Maas, Jeroen
Abstract : Purpose: – In general, active participation increases learning outcomes. The purpose of this paper is to explore how: information and communication technologies (ICT) can be used to improve the participation of students during lectures and the effect of ICT on the learning outcomes of students. Design/methodology/approach: – The authors tested a specific tool, Soapbox, in a compulsory course of a Masters' program, at VU University, The Netherlands. During half of the lectures the students were invited to participate using their mobile phone or laptop, for the other half of the lectures, taught by the same lecturer, the tool was not used. The authors compared the two groups of lectures. For the evaluation the authors used observations in the classroom, a questionnaire, in-depth interviews, and focus group discussions with students and with the lecturer. Findings: – The results show that the ICT tool facilitated and increased the level of communication and interaction among the students and between the students and the lecturers. Students' scored lectures with the tool consistently higher on the item "engaging." Most of the students appreciated the use of the ICT tool and said that they felt more involved. Originality/value: – Despite the knowledge about the limited learning effect of lectures on larger groups, most of the teaching at universities is conducted through such lectures. The research shows that the majority of the students felt more involved in the lectures with the ICT tool, and almost half of the students feel that the learning effect of lectures with the tool is higher than the learning effect of lectures without. Although observations could not confirm the perceived enhanced involvement, about 80 percent would recommend using the tool in other classes, providing a case for the use of interactive technology in large-scale lectures.